Optimization of a self-excited pulsed air-water jet nozzle based on the response surface methodology - Wang, Yong (Strojniški vestnik, 2021)
A self-excited pulsed air-water jet (SEPAWJ) offers many advantages over other jets and has a large number of practical and industrial applications. In order to take better advantage of the SEPAWJ, response surface methodology (RSM) models were established with the experimental impact force characteristics as the dependent variable and three key nozzle parameters as the independent variable. Single and coupling factor effects of these three parameters (oscillation chamber length, oscillation chamber height, and diameter of the downstream nozzle) on performance of nozzle are analysed, and the structural parameters of optimum performance are calculated using RSM models. The external flow field, impact force and cleaning performance of SEPAWJ before and after optimization are analysed and compared experimentally. It is found that the significance levels of established average impact force and impact force amplitude RSM models are lower than 0.05, and their error ratios between calculation and experiment under the optimum construction are both less than 5 %, which confirms their considerable reliability. Meanwhile, the final large water mass of optimized SEPAWJ is formed much earlier, and is more intensive and more concentrated. Compared with the original SEPAWJ nozzle, the impact force and impact force amplitude of optimized SEPAWJ nozzle are increased by 52.00 % and 38.26 %, respectively. In addition, the cleaned area ratio of nozzle before and after optimization is 76 % and 100 % at 50 seconds, respectively, with an increase of 22.4 %.
Keywords: cleaning performance; curek; impact force; metoda odzivnih ploskev; multiphase flow; optimizacija; optimization; pulsed jet; učinek čiščenja; udarna sila; večfazni tok